The Long-Run Equilibrium of Industry Population and Bottom Lines: Analysing the Near-Perfect Restaurant Industry - Opstad, Leiv; Valenta, Robin (Journal of Applied Business and Economics, 2022)
The establishment and bankruptcy of businesses is a crucial aspect of the market economy. The market in which restaurants compete is characterized by few barriers to entry, strong competition, low marginal rates of profit, and high levels of bankruptcy. Using publicly available panel data of all Norwegian restaurants, we examine the determinants of market levels of entry and exit. In theory, the driving force in the space of market turnover is the marginal rate of profit in the industry. There is a strong link between the profit rates in the sector and number of firms leaving and entry the marked.